Just Buying the Peace? : Subnational Spending, Institutional Innovation, and the Political Order in Timor-Leste - Akmeemana, Sakuntala (World Bank, Washington, DC, 2019)
In the wake of the country’s political crisis and ensuing outbreak of violence in 2006, the newly elected government of Timor-Leste embarked upon a fivefold increase in public spending. This initiative is widely seen as an exemplar of ‘buying the peace’, in this case, deploying petroleum wealth for the sole purpose of ‘offering cash payments and contracts to potential spoilers.’ This paper focused on the political, economic, and social conditions in the aftermath of the conflict that led elites to invest in institutions and governing domains where crucial social contests were occurring.